Sortilin enhances fibrosis and calcification in aortic valve disease by inducing interstitial cell heterogeneity. (20th January 2023) - Iqbal, Farwah; Schlotter, Florian; Becker-Greene, Dakota; Lupieri, Adrien; Goettsch, Claudia; Hutcheson, Joshua D; Rogers, Maximillian A; Itoh, Shinsuke; Halu, Arda; Lee, Lang Ho; Blaser, Mark C; Mlynarchik, Andrew K; et al.
Abstract: Aims: Calcific aortic valve disease (CAVD) is the most common valve disease, which consists of a chronic interplay of inflammation, fibrosis, and calcification. In this study, sortilin (SORT1) was identified as a novel key player in the pathophysiology of CAVD, and its role in the transformation of valvular interstitial cells (VICs) into pathological phenotypes is explored. Methods and results: An aortic valve (AV) wire injury (AVWI) mouse model with sortilin deficiency was used to determine the effects of sortilin on AV stenosis, fibrosis, and calcification. In vitro experiments employed human primary VICs cultured in osteogenic conditions for 7, 14, and 21 days; and processed for imaging, proteomics, and transcriptomics including single-cell RNA-sequencing (scRNA-seq). The AVWI mouse model showed reduced AV fibrosis, calcification, and stenosis in sortilin-deficient mice vs. littermate controls. Protein studies identified the transition of human VICs into a myofibroblast-like phenotype mediated by sortilin. Sortilin loss-of-function decreased in vitro VIC calcification. ScRNA-seq identified 12 differentially expressed cell clusters in human VIC samples, where a novel combined inflammatory myofibroblastic-osteogenic VIC (IMO-VIC) phenotype was detected with increased expression of SORT1, COL1A1, WNT5A, IL-6, and serum amyloid A1. VICs sequenced with sortilin deficiency showed decreased IMO-VIC phenotype. Conclusion: Sortilin promotes CAVD by mediating valvular fibrosis and calcification, and a newly identified phenotype (IMO-VIC). This is the first study to examine the role of sortilin in valvular calcification and it may render it a therapeutic target to inhibit IMO-VIC emergence by simultaneously reducing inflammation, fibrosis, and calcification, the three key pathological processes underlying CAVD. Structured Graphical Abstract: Structured Graphical Abstract Multi-omic approach to identify the role of sortilin in mediating fibrosis and calcification in calcific aortic valve disease (CAVD). Aortic valve (AV) wire injury in sortilin wild-type (Sort1 +/+ ) and deficient mice (Sort1 −/− ) showed decreased collagen deposition and calcification in mouse AVs. Valvular interstitial cells (VICs) were collected from human CAVD tissue and cultured in osteogenic conditions. VICs collected at varying time points of culture (Days 7, 14, and 21) were processed for flow cytometry, proteomics, and single-cell RNA-sequencing (scRNA-seq). Multiomics data identified increased sortilin expression following the osteogenic culture of VICs. Protein analysis and scRNA-seq identified increased expression of WNT5a, MAPK, YAP, and IL-6 regulated by the expression of sortilin. ScRNA-seq identified a transitionary VIC subpopulation with an activated myofibroblast phenotype that later transitioned into a combined myofibroblast and osteogenic phenotype. ScRNA-seq data identified an inflammatory myofibroblastic-osteogenic VIC (IMO-VIC) subpopulation that may be a key player in the pathogenesis of CAVD under the regulation of sortilin.